2017
DOI: 10.1371/journal.pone.0186924
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with proteasome inhibitor bortezomib decreases organic anion transporting polypeptide (OATP) 1B3-mediated transport in a substrate-dependent manner

Abstract: OATP1B1 and OATP1B3 mediate hepatic uptake of many drugs (e.g., statins) and can mediate transporter-mediated drug-drug-interactions (DDIs). Bortezomib is the first-in-class proteasome inhibitor drug approved by the U. S. Food and Drug Administration for the treatment of multiple myeloma. The potential of bortezomib to cause OATP-mediated DDIs has not been assessed. The current study investigated the involvement of the ubiquitin-proteasome system (UPS) in OATP1B1 and OATP1B3 degradation and determined the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Ubiquitination is an important post-translational modification that regulates many cellular processes including signal transduction, cell cycle control and transcriptional regulation through mediating proteasome degradation of proteins and the maintenance of protein homeostasis [ 137 ]. A recent study reported that both OATP1B1 and OATP1B3 can be ubiquitin-conjugated in HEK293 cells over-expressing OATP1B1 or OATP1B3 [ 138 ]. However, the effects of ubiquitination on OATP1B1 and OATP1B3 transport function have not been demonstrated and further studies are warranted.…”
Section: Post-translational Regulation Of Oatp1b1 and Oatp1b3mentioning
confidence: 99%
See 3 more Smart Citations
“…Ubiquitination is an important post-translational modification that regulates many cellular processes including signal transduction, cell cycle control and transcriptional regulation through mediating proteasome degradation of proteins and the maintenance of protein homeostasis [ 137 ]. A recent study reported that both OATP1B1 and OATP1B3 can be ubiquitin-conjugated in HEK293 cells over-expressing OATP1B1 or OATP1B3 [ 138 ]. However, the effects of ubiquitination on OATP1B1 and OATP1B3 transport function have not been demonstrated and further studies are warranted.…”
Section: Post-translational Regulation Of Oatp1b1 and Oatp1b3mentioning
confidence: 99%
“…In OATP1B1- and OATP1B3-expressing stable cell lines and human SCH, treatment with lysosome inhibitor chloroquine markedly increased protein levels of OATP1B1 and 1B3, suggesting that the lysosome plays an important role in degradation of OATP1B1 and OATP1B3 [ 138 , 161 ]. The estimated maximum unbound concentration of chloroquine at the inlet to the liver is ~56.8 μM after a 600 mg single dose in human [ 161 ].…”
Section: Regulation Of Oatp1b1/1b3 Transport Function By Drugs Permentioning
confidence: 99%
See 2 more Smart Citations
“…Carfilzomib inhibited the chymotrypsin-like activity of the 20S proteasome in the kidney by 50~60% in rats (FDA, 2012). Recent studies showed that bortezomib can affect the activities of copper transporter 1, ATP-binding cassette transporter A1 (ABCA1) and ABCG1, metal transporter ZIP14 and organic anion transporting polypeptide (OATP) 1B3 (Alam et al, 2017;Jandial et al, 2009;Ogura et al, 2011;Zhao et al, 2014). However, the potential of these antitumor drugs to modulate OAT1 activity has not been explored.…”
Section: Discussionmentioning
confidence: 99%